Two-dimensional square-pyramidal VO2 with tunable electronic properties. Issue 13 (18th February 2015) - Tang, Zhen-Kun; Li, Xi-Bo; Zhang, Deng-Yu; Zhang, Yan-Ning; Liu, Li-Min
Abstract : In order to design the high-performance spintronics, it is rather critical to develop new materials, which can easily regulate the magnetism of nanostructures. Abstract : In order to design the high-performance spintronics, it is rather critical to develop new materials, which can easily regulate the magnetism of nanostructures. In this work, the electronic properties of two dimensional (2D) square-pyramidal vanadium dioxide (S-VO2 ) are explored based on first-principles calculations. The results reveal that the monolayer S-VO2 is an ideal flexible platform to manipulate the magnetic properties by either biaxial compressive strain or surface modification. Although the ground state of the pristine S-VO2 is a direct semiconductor with antiferromagnetic (AFM) coupling between two nearest V atoms, the monolayer S-VO2 becomes ferromagnetic (FM) under a biaxial compressive strain. Furthermore, the monolayer S-VO2 can be tuned from a nonmagnetic semiconductor to a magnetic semiconductor and even to a half-metal through surface modification. The tunable magnetic properties of the monolayer S-VO2 make it a promising candidate for applications in spin-devices.